Polycarbonate and polystyrene nanoplastic particles act as stressors to the innate immune system of fathead minnow (Pimephales promelas). (18th July 2016) - Greven, Anne‐Catherine; Merk, Teresa; Karagöz, Filiz; Mohr, Kristin; Klapper, Markus; Jovanović, Boris; Palić, Dušan
Abstract: Water pollution with large‐scale and small‐scale plastic litter is an area of growing concern. Macro‐plastic litter is a well‐known threat to aquatic wildlife; however, the effects of micro‐sized and nano‐sized plastic particles on the health of organisms are not well understood. Small‐scale plastic particles can easily be ingested by various aquatic organisms and potentially interfere with their immune system; therefore, the authors used a freshwater fish species as a model organism for nanoplastic exposure. Characterization of polystyrene (41.0 nm) and polycarbonate (158.7 nm) nanoplastic particles (PSNPs and PCNPs, respectively) in plasma was performed, and the effects of PSNPs and PCNPs on the innate immune system of fathead minnow were investigated. In vitro effects of PSNPs and PCNPs on neutrophil function were determined using a battery of neutrophil function assays. Exposure of neutrophils to PSNPs or PCNPs caused significant increases in degranulation of primary granules and neutrophil extracellular trap release compared to a nontreated control, whereas oxidative burst was less affected. The present study outlines the stress response of the cellular component of fish innate immune system to polystyrene and polycarbonate nanoparticles/aggregates and indicates their potential to interfere with disease resistance in fish populations. Environ Toxicol Chem 2016;35:3093–3100. © 2016 SETAC